Relevance of budgerigars (Melopsittacus undulatus) in experimental epidemiology of newcastle disease - Denadai, Janine [UNESP]; Paulillo, Antonio Carlos [UNESP]; Martins, Gislaine Regina Vieira [UNESP]; dos Santos Schmidt, Elizabeth Moreira [UNESP]; Carrasco, Adriano Torres (My University, 2011)
This study was carried out to clarify the real role that was played by the budgerigars (Melopsittacus undulatus) in the epidemiological plan, under the perspective of its being an infection source of the Newcastle Disease Virus (NDV). For this, the study used Specific-Pathogen-Free chicks (SPF) that were housed with budgerigars that were inoculated with a pathogenic strain (velogenic viscerotropic) of NDV (EID 50 = 10 8,5/0.1 ml) pathogenic to chickens, by the ocular-nasal via. Each group was composed by 10 SPF chicks and 5 budgerigars. After 5 days of the inoculation of the budgerigars with NDV, SPF chicks were put together with each group of budgerigars, so that there was a direct contact between both species. Cloacal swabs and blood samples were collected in both species (budgerigars and SPF chicks) after 13 and 19 days post-challenge, respectively, for genome viral excretion by Reverse Transcription Polymerase Chain Reaction (RT-PCR) and antibody's search by the inhibition of hemmaglutination test (HI). Budgerigars did not demonstrate any clinical signs of Newcastle Disease (ND). They were refractory to the clinical disease with the NDV. However, antibody titres from inhibition of Hemagglutination (HI) test were detected 9 and 21 days after challenge. Therefore, it was demonstrated the state of carrier of NDV in this species. In SPF chicks allocated with infected budgerigars, NDV genome was detected 13 and 19 days after challenge. Thus, the transmission of the pathogenic virus from the budgerigars to SPF chicks that were housed together was evident until 19 days of the experimental infection with this pathogen. This reveals the importance of the budgerigars from the epidemiological point of view as a potential source of infection of the NDV to commercial chickens that could be raised near this species. © Asian Network for Scientific Information, 2011.
Keywords: Budgerigars; Epidemiology; Melopsittacus undulatus; NDV carrier; Newcastle disease; Source of infection of the NDV